Study of transmission electrical machines (2009)
As an alternative in the energetic utilization of energy of  periodical nature, it becomes a study of generators to use directly the movements translational, without the need to make conversions to rotational energy. The operation of the generator is based on the law of induction of Faraday, in the same way that makes all the electrical machines. This document is focused on the use of the waves as part of the tidal power, it is therefore requires the implementation of some concepts of the hydrostatic and statistical data of the waves for a supposed place of mounting the machine. With the previous information is developed a program in Matlab® to provide the necessary data for the subsequent design of the machine.